Knowledge-Based Information Retrieval System for Construction Industry : Applying Knowledge Management Concept in Small and Medium Enterprise - Ismail, Shahrinaz; Zulkhafli, Nurul Nabila (Journal of Computing Technologies and Creative Content, 2020)
Knowledge management (KM) is the process of making the best use of knowledge and information within an organization to achieve business objectives. It allows people to access and apply the most appropriate knowledge when it is needed and supports learning. Knowledge-Based Information Retrieval System is one of the tools built for small and medium enterprises (SMEs), especially for construction companies that need to manage information in their abundance of explicit documents that are dependent to the employees’ tacit knowledge. Through this system, the employees can share their explicit and implicit knowledge in the knowledge management system, which is developed with the concept of knowledge-based information retrieval. The development of this system will ease employees’ work in the company in terms of retrieving information, sharing knowledge, leveraging knowledge management, and so on. The main function of the Knowledge-Based Information Retrieval (KBIT) system is to enable users to search for files related to project or tender, or files needed at that time by project name or by location. Besides that, users can view the files and scroll the documents through the system interface. This system will bring a significant impact to the users, who consist of the administrator and employees. In addition to that, it will improve the business process and ensure efficiency in the company’s business value chain. The important contribution of this system is in terms of reducing waste of time to search for files.